The utility of 1-Minute sit-to-stand test to detect exercise-induced oxygen desaturation in outpatient assessment of post COVID-19 patients / Muhammad Amin Ibrahim ... [et al.] - Ibrahim, Muhammad Amin; Shee, Chai Chee; Kamaridin, Mohd Nazeri; Abdul Rani, Mohammed Fauzi (Faculty of Medicine, 2024)
Introduction: 6-min-walk-test (6MWT) is the gold standard for assessing exercise-induced impairment of gas exchange, but it is technically challenging in a busy outpatient clinic. The aim of this study was to compare the 1-minute sit-to-stand test (1MSTST) with the 6MWT in assessment of exercise-induced oxygen desaturation in post COVID-19 patients in an outpatient setting. Methods: A total of 447 outpatient post COVID-19 patients were recruited from post COVID-19 clinic. A set of 6MWT and 1MSTST were performed on the same day. Results: A total of 447 sets were performed at a mean of 160 days post discharge. Majority were in COVID-19 infection category 4 (n=251, 56%), 5 (n=118, 26%) and 3 (n=6, 15%). A total of 19% (n=89) of patients remained symptomatic (mMRC >1). There were no significant differences between nadir SpO2 of 6MWT and 1STST (p=0.075). Bland-Altman plots showed good agreement between nadir SpO2 for 6MWT and 1MSTST (Mean differences=0.028). 1MSTST could detect oxygen desaturation >4% with sensitivity of 76.8% and specificity of 42.4% compared to 6MWT. There was no clinically significant SpO2 difference during 6MWT and 1STS between symptomatic and asymptomatic patients at baseline, nadir, and recovery; the differences were <1%. However, there were lesser 6MWT distance and 1MSTST repetition between symptomatic and asymptomatic patients; 47m (p < 0.001) and 3 repetition (p < 0.001) respectively. Conclusion: There is a good agreement of nadir SpO2 and sensitivity to detect oxygen desaturation > 4% between 6MWT and 1MSTST. 1MSTST is a useful screening test to screen exercise-induced oxygen desaturation during outpatient assessment.